2017
DOI: 10.1001/jamafacial.2016.2153
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanic Factors Associated With Orbital Floor Fractures

Abstract: lowout fractures of the orbit, a term first put forth by Smith and Regan, 1 describes a specific set of fractures of the orbital bone often resulting from blunt trauma. Most commonly this refers to fractures of the orbital floor but can also include the medial orbital wall or the roof of the orbit. To further explain the mechanism underlying this type of fracture, the "buckling" theory and the "hydraulic" theory have been previously proposed. 2,3 The buckling theory contends that injury-but not fracture-to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 11 publications
0
20
0
20
Order By: Relevance
“…Interestingly, the energies of the impact during the hydraulic mechanism causing the orbital wall damage reported by almost all other authors are unquestionably lower than those observed in the current work. Exempli gratia, according to simulations of Nagasao et al, the impact energy of 0.933 J is believed to initiate the fracture within the orbit for hydraulic mechanism [ 11 ], while the computations of Patel et al showed that the impact energies causing both lower and medial wall fractures were from the range of 3.0–5.0 J [ 6 ]. On the contrary to the above values, the calculated total strain energy corresponding to the very first moment of exceeding the applied H-M-H limit in the current model (MOBOSE) was 16.4 J.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the energies of the impact during the hydraulic mechanism causing the orbital wall damage reported by almost all other authors are unquestionably lower than those observed in the current work. Exempli gratia, according to simulations of Nagasao et al, the impact energy of 0.933 J is believed to initiate the fracture within the orbit for hydraulic mechanism [ 11 ], while the computations of Patel et al showed that the impact energies causing both lower and medial wall fractures were from the range of 3.0–5.0 J [ 6 ]. On the contrary to the above values, the calculated total strain energy corresponding to the very first moment of exceeding the applied H-M-H limit in the current model (MOBOSE) was 16.4 J.…”
Section: Discussionmentioning
confidence: 99%
“…Worth noting, the novel element of the current investigation is the successful attempt to model the blowout type of trauma as the orbit was loaded indirectly via the contact interactions of the intraorbital soft tissues subjected to the set of forces directly, unlike what other authors did such as Al-Sukhun et al [ 7 , 13 , 30 ], Schaller et al [ 12 ], Patel et al [ 6 ], and Foletti et al [ 8 , 9 ]. Those models concern the blunt type of impact when a rigid/deformable body collided with a deformable model of a human skull.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many factors affecting the results of surgery, including the timing of surgery, repair materials, and surgical approach (6)(7)(8)(9). Most orbital fractures do not require immediate repair, depending on the severity and type of fracture.…”
Section: Introductionmentioning
confidence: 99%